KINERJA KARYAWAN BANDAR UDARA ADI SOEMARMO SURAKARTA - Ranumi Wijaya; Vica Nurhayati Harahap; Salahudin Rafi (Institut Transportasi dan Logistik Trisakti, 2018)
The purpose of the study was to examine the effect of leadership style and motivation at work to the employees’ performance of PT. Angkasa Pura I (Persero) at Adi Soemarmo Airport in Surakarta. The quantitative method was used in this study. The analysis was using simple and multiple linear regressions. The sample was 33 employees of Airport Operation Service and Hospitality division at the airport. The result of the study are (1) the leadership style positively and significantly effects the employees’ performance of 94.4 %, (2) the motivation at work positively and significantly effects the employees’ performance of 88.4 %, and (3) simultaneously both the leadership style and motivation at work positively and significantly effects the employees’ performance of 95.2 %.